Intraoperative Parathyroid Hormone Assessment in Patients with Primary Hyperparathyroidism – One–Year Experience: Intraoperativno določanje paratiroidnega hormona pri bolnikih s primarnim hiperparatiroidizmom – naše enoletne izkušnje - Greif, Boris; Hojski, Aljaž; Crnjac, Anton (Acta Medico-Biotechnica, 2021)
Purpose: We evaluated our one– year experience in the intraoperative measurement of parathyroid hormone (IOPTH) in parathyroid adenoma surgery. We also compared surgical outcome after minimally invasive parathyroidectomy (MIP) and conventional neck exploration (CNE).Methods: Between April 2011 and April 2012, eight consecutive patients with primary hyperparathyroidism (PHP) underwent parathyroidectomy with IOPTH in our institution. Parathyroidectomy was defined as successful when a >50% decrease of IOPTH was observed 10 minutes after resection of the abnormal gland. The second criterion for success was a six month period of postoperative normocalcaemia.Results: We performed four MIPs, two unilateral neck explorations, and two bilateral neck explorations, resulting in a total of seven solitary and one double adenomas. IOPTH level decrease expectations were met in all cases. The average length of surgery for MIP was 31 minutes, and 69 minutes for CNE. All patients were eucalcaemic with normal PTH levels during the 6 month follow–up period. Three patients had postoperative hypocalcaemia after CNE and there were no recurrences 6 months postoperatively.Conclusion: The review of our series of eight consecutive patients with PHP showed a 100% cure rate after employing IOPTH measurement in both surgical approaches. The advantages of MIP are: shorter operating time, better cosmetic results, and a lower incidence of hypocalcaemia.
Keywords: parathyroid adenoma; parathyroidectomy; intraoperative parathyroid hormone level; surgical outcome